Morphology Control in co-evaporated bulk heterojunction solar cells - Kovacik, P; Assender, H; Watt, A (Elsevier, 2013)
Bulk heterojunction solar cells made by vacuum co-evaporation of polythiophene (PTh) and fullerene (C60) are reported and the blend morphology control through donor-acceptor composition and post-situ annealing demonstrated. Co-deposited heterojunctions are shown to generate about 60% higher photocurrents than their thickness-optimized PTh/C60 planar heterojunction counterparts. Furthermore, by annealing the devices post-situ the power conversion efficiency is improved by as much as 80%. UV-vis, XRD and AFM analysis shows that the enhanced photoresponse is a result of favorable morphological development of PTh upon annealing. Annealing-induced improvement of the donor-acceptor network is demonstrated across a wide range of compositions (20-80% PTh). This illustrates that good morphology control is possible in co-evaporated polymer-fullerene blends through multiple parameters and differentiates this donor-acceptor combination from the standard small-molecule systems. © 2013 The Authors.